2011
DOI: 10.1093/carcin/bgr213
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-499-5p promotes cellular invasion and tumor metastasis in colorectal cancer by targeting FOXO4 and PDCD4

Abstract: MicroRNAs (miRNAs) regulate tumor progression and invasion via direct interaction with target messenger RNAs (mRNAs). We defined miRNAs involved in cancer metastasis (metastamirs) using an established in vitro colorectal cancer (CRC) model of minimally metastatic cells (SW480 line) from a colon adenocarcinoma primary lesion and highly metastatic cells (SW620 line) from a metastatic lymph node from the same patient 1 year later. We used microarray analysis to identify miRNAs differentially expressed in SW480 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 46 publications
1
97
2
Order By: Relevance
“…FOXO4 and PDCD4 have been identified as direct and functional targets of miR-499-5p. These findings indicate that miR-499-5p promotes metastasis of CRC cells and may be useful as a potential therapeutic target for CRC [18].…”
Section: Therapeutic Approaches Based On Metastasis-related Mirnasmentioning
confidence: 76%
See 1 more Smart Citation
“…FOXO4 and PDCD4 have been identified as direct and functional targets of miR-499-5p. These findings indicate that miR-499-5p promotes metastasis of CRC cells and may be useful as a potential therapeutic target for CRC [18].…”
Section: Therapeutic Approaches Based On Metastasis-related Mirnasmentioning
confidence: 76%
“…Silencing of miR-181 leads to a reduction in the motility and invasion of hepatocellular CSCs [5] miR-193a Increase in p53-deficient tumors p53 Chemotherapy causes p63/p73-dependent induction of miR-193a-5p, thereby limiting chemosensitivity due to miRNA-mediated feedback inhibition of p73 [4] miR-199a/b Decrease in HCC PAK4 Suppresses HCC growth through inhibiting PAK4/ Raf/MEK/ERK pathway both in vitro and in vivo [15] miR-200a Decrease in pancreatic cancer DCAMKL-1 siRNA-mediated knockdown of DCAMKL-1 in cancer cells induces miR-200a along with downregulation of EMT-associated transcription factors ZEB1, ZEB2, Snail, Slug and Twist [23] miR-340 Decrease in aggressive breast cancer c-Met Suppresses tumor cell migration and invasion through the regulation of MMP-2 and MMP-9 expression [19] miR-342 Decrease in CRC DNMT1 Dramatically reduces DNMT1 expression, which in turn reactivates ADAM23, Hint1, RASSF1A and RECK genes via promoter demethylation [10] miR-488* Decrease in PCa AR Downregulates the transcriptional activity of AR and inhibits the endogenous AR protein production [16] miR-499 Increase in highly invasive CRC FOXO4, PDCD4 Promotes CRC cell migration and invasion in vitro as well as lung and liver metastasis in vivo [18] miR-516a Decrease in highly metastatic GC Sulfatase 1 Atelocollagen-mediated delivery of a miR-516a-3p expression vector into orthotopic highly metastatic tumors may have a therapeutic application in blocking metastatic dissemination of GCs [22] miR-520b HBXIP [20] AR Thus miR-193a inhibition may provide a new therapeutic opportunity in p53-deficient tumors [4]. Cancer stem cells (CSCs) hold the extensive proliferative and self-renewal potential necessary to develop cancer.…”
Section: Rassf1a Timp3 Nlkmentioning
confidence: 99%
“…Wang' et al also found that serum microRNA-29a is a promising novel marker for early detection of colorectal liver metastasis [23]. The metastasis-inhibiting miRNAs (miR-342, 320a, 135a, miR-139, etc) in CRC are identified [24,25,26,27], while some metastasis-promoting miRNAs (miR-499-5p, miR-103/107, miR-155, etc) are also reported [28,29,30]. Has-miR-149, located on chromosome 2, has proven to be an essential miRNA implicated in the development and the progression of human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that miRNA could be related to 200 genes, and play a key role in gene regulation and physiologic and pathologic processes, such as tumorignesis, cell proliferation, apoptosis and metabolism (He and Hannon, 2004;Krek et al, 2005;Johnnidis et al, 2008;Aumiller and Forstemann, 2008;Mocellin et al, 2009;Zhou et al, 2010). A previous experimental study indicated that MiRNA has a key influence on tumor biology and is related to the progression and prognosis of cancer, and that the high expression of miR-499A>G in serum was significantly associated with a longer survival of non-small cell lung cancer (Hu et al, 2010;Liu et al, 2011). Common single nucleotide polymorphisms in premiRNA, rs3746444 in miR-499A>G and rs2910164 in miR-146aG>C, have been studied in various cancers, such as breast cancer, gastric cancer, cervical squamous cell cancer and colorectal cancer (Catucci et al, 2010;Okubo et al, 2010;Gao et al, 2011;Zhou et al, 2011;Srivastava and Srivastava, 2012;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%